A cross sectional study on menstrual hygiene and associated factors among high school girls in rural Mysuru - Nimithamohan, K.; Murthy, M. R. Narayana; L., Divya K.; ., Amoghashree (International Journal Of Community Medicine And Public Health, 2022)
Background: Menstruation marks the start of a girl's reproductive life and is a significant process in her life. Women’s menstrual cycle is directly or indirectly impacted by diet and physical activity. Menstruating women's health and social lives are negatively impacted by a lack of understanding of physiology, an unscientific attitude, myths, and misconceptions. Despite the array of initiatives put up so far, a myriad of challenges remains to be addressed. The study aims to estimate the menstrual hygiene practices, and associated factors among rural high school girls in mysuru. Methods: A cross sectional study was conducted among 200 rural high school girls from January to March 2022 in rural Mysuru. A pretested and semi structured questionnaire was used for collecting data and analysed using SPSS software version 25. Results: The mean age of the study participants was 13.8±0.9 years. Out of 200 adolescent girls, 107 (59.4%) had attained menarche at 10-12 years of age. 61.7% of them reported having abdominal pain during menstruation. 71.1% of the girls reported that their diet was altered during menstruation. Only 37.5% of the study participants do regular exercise. Conclusions: The present study showed that the majority of the girls’ diet and physical activity altered after menarche and during menstruation. A focused intervention like behavioural change communication involving the high importance of consumption of fruits and vegetables, iron and calcium rich foods, avoidance of skipping meals, and taking healthy foods should be encouraged.